2016
DOI: 10.5152/iao.2016.1770
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss in Persons Exposed and not Exposed to Occupational Noise

Abstract: OBJECTIVE:This study aimed to compare hearing loss in individuals at risk and those not at risk for occupational noise and to compare working loss by gender. MATERIALS and METHODS:The analysis used data from a current Czech Ministry of Health grant project called Epidemiological and Genetic Study of the Frequency of Hearing Loss (2011Loss ( to 2015 NT12246-5/2011). The analyzed sample comprised 4988 participants. Hearing was tested using pure-tone threshold audiometry, tympanometry, and measurement of the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
1
13
0
1
Order By: Relevance
“…Adverse health effects with exposure to occupational noise are of increasing health concern. Hearing loss is a well-known consequence of long-term exposure to high level noise 6 , 7 , and occupational noise exposure has also been associated with sleeping disorders 8 , ECG abnormalities 9 or hypertension 10 . Persistent damage on hair cells and hearing conduction nerves induced by long-term exposure to relative high level of occupational noise was thought to be a key reason for hearing loss 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Adverse health effects with exposure to occupational noise are of increasing health concern. Hearing loss is a well-known consequence of long-term exposure to high level noise 6 , 7 , and occupational noise exposure has also been associated with sleeping disorders 8 , ECG abnormalities 9 or hypertension 10 . Persistent damage on hair cells and hearing conduction nerves induced by long-term exposure to relative high level of occupational noise was thought to be a key reason for hearing loss 11 .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] This association is partly biased by the cumulative noise exposure inherent to an increasing age. Second, several studies on occupational NIHL 9,10,[12][13][14] have shown that men are more likely to develop NIHL than are women. For the same amount of occupational noise, Kovalova et al 13 observed significantly more NIHL in men than in women.…”
mentioning
confidence: 99%
“…Second, several studies on occupational NIHL 9,10,[12][13][14] have shown that men are more likely to develop NIHL than are women. For the same amount of occupational noise, Kovalova et al 13 observed significantly more NIHL in men than in women. Third, alcohol intake is correlated with NIHL.…”
mentioning
confidence: 99%
“…Between January 2013 and August 2017, a sample of 1611 subjects (769 males, 842 females; average age 73.8 years, SD ± 6), living independently or institutionalized, was randomly selected from the electoral rolls of eight Italian municipalities after stratification for age and gender. All subjects are part of "The Great-AGE Study", an on-going population-based study on ageing conducted in Castellana Grotte, a small town in the Apulia region, southern Italy [38]. The study population was divided into a group of subjects exposed professionally to noise for a period of less than 10 years or not at all (n = 1129) and a group of subjects professionally exposed to noise for over 10 years (n = 482).…”
Section: Methodsmentioning
confidence: 99%